2016
DOI: 10.1557/mrc.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory investigation of the electronic structure and defect chemistry of Sr1-xKxFeO3

Abstract: Solid oxide fuel cells (SOFCs) efficiently generate electricity, but high operating temperatures (T op > 800°C) limit their utility. Reducing T op requires mixed ion-electron conducting (MIEC) cathode materials. Density functional theory is used here to investigate the role of potassium substitutions in the MIEC material Sr 1−x K x FeO 3 (SKFO). We predict that such substitutions are endothermic. SrFeO 3 and SKFO have nearly identical metallic electronic structures. Oxygen vacancy formation energies decrease b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[27][28][29] The high degree of compositional control provided by ALD of Fe 2 O 3 may allow titration of the Sr in the form of SrFeO 3 and re-activation of the electrode. 30,31 Finally, we suggest that ALD has great promise for producing electrodes with complex and potentially promising surface structures. Here, we demonstrated that both pure and mixed-oxide films can be grown, but more complicated structures can be imagined.…”
Section: Discussionmentioning
confidence: 95%
“…[27][28][29] The high degree of compositional control provided by ALD of Fe 2 O 3 may allow titration of the Sr in the form of SrFeO 3 and re-activation of the electrode. 30,31 Finally, we suggest that ALD has great promise for producing electrodes with complex and potentially promising surface structures. Here, we demonstrated that both pure and mixed-oxide films can be grown, but more complicated structures can be imagined.…”
Section: Discussionmentioning
confidence: 95%